Recent decrease in inner‐core rain rate of tropical cyclones over the western North Pacific - Na Wei; Jinjie Song; Yifei Dai; Sulin Jiang; Yihong Duan (Atmospheric Science Letters, 2022)
Abstract The tendency in tropical cyclone (TC) rainfall is of great concern due to its remarkable contribution to global precipitation and extreme rainfall events. This study finds a decreasing trend in TC inner‐core rain rate over the western North Pacific (WNP) from 1998 to 2019. This basinwide trend is mainly induced by the decreasing TC inner‐core rain rates over the region west of 150°E, while it is seldom linked to the changes in the distribution of TC occurrence. The maximum decreases in TC inner‐core rain rate are observed over the offshore areas along the coastlines of East Asia. Further analysis reveals that the change in atmospheric stability, referred to as a dominant environmental contributor to basinwide TC inner‐core rain rate decreases shown in previous studies, only has a primary impact over the northern South China Sea. By comparison, there is a positive correlation between the variations of the aerosol optical depth and TC inner‐core rain rate over the mid‐latitude regions extending from the East China Sea to Japan. Our result highlights the linkage of the recent decreasing trends in aerosol optical depth and TC inner‐core rain rate over the WNP.